Non-voting preferred shares in Portugal: a general overview - Pessoa, Diogo (2022)
In this article we intend to provide a general overview of the Portuguese legal framework regarding the non-voting preferred shares (NVPS). We have also highlighted some of the issues and concerns that may be the reason to justify the almost no use of such shares.